2021
DOI: 10.1149/2.f08211if
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis as a Design Variable for Oxide Materials

Abstract: When studying a new electrochemical couple, numerous variables affect how it is evaluated, how successful it is judged to be, and system properties. In the energy storage field, many researchers evaluate materials using performance metrics that might include capacity, rate capability, or cell impedance values to assess various cell chemistries. Behind these numbers are underlying attributes such as particle morphology, tap density, particle size, surface functionality, and even growth facet that are influenced… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…For the single-stage heating cycles, the extent of relithiation either was insufficient (i.e., temperature too low) or resulted in loss of lattice integrity via oxygen loss and surface reduction to binary or alternative phases. However, based on an understanding of continuous stirred tank reactors and other commercial synthesis methods, multi-stage processes that allow separation of the lithium source activation, followed by equilibration and integration, are advantageous for the isolation of homogeneous materials . We have shown that in the recycling process for NMC cathodes, a superior (electrochemical cycling, cation homogeneity) final recycled material is isolated using a two-stage process that allows for the decomposition of the lithium hydroxide hydrate and diffusion with integration into the lattice before vacancies collapse or secondary phases form.…”
Section: Electrochemical Evaluationmentioning
confidence: 99%
“…For the single-stage heating cycles, the extent of relithiation either was insufficient (i.e., temperature too low) or resulted in loss of lattice integrity via oxygen loss and surface reduction to binary or alternative phases. However, based on an understanding of continuous stirred tank reactors and other commercial synthesis methods, multi-stage processes that allow separation of the lithium source activation, followed by equilibration and integration, are advantageous for the isolation of homogeneous materials . We have shown that in the recycling process for NMC cathodes, a superior (electrochemical cycling, cation homogeneity) final recycled material is isolated using a two-stage process that allows for the decomposition of the lithium hydroxide hydrate and diffusion with integration into the lattice before vacancies collapse or secondary phases form.…”
Section: Electrochemical Evaluationmentioning
confidence: 99%